PERAN STANDAR KOMPETENSI TERHADAP KINERJA KARYAWAN DI PUSAT PERPUSTAKAAN DAN PENYEBARAN TEKNOLOGI PERTANIAN (PUSTAKA) BOGOR - Vonny Tiara Narundana (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Human resources and flexible government system toward environmental change areincreasingly decisive to get success in goal achieving. Competence is an important factor forperformance, but that alone have not been adequate in building the effectiveness. Performance isinfluenced by environment of organization involving its process and system. This study was conductedat the office of Indonesian Center for Agricultural Library and Technology Dissemination (PUSTAKA),Bogor.The subject of this study was employee of PUSTAKA office and census was used as thetechnic of sampling. Thus, the number of samples were 88 employees who are its whole population.Data was analyzed by SEM (Structural Equation Model) using PLS program. From the result, it was ableto conclude that competence influenced performance positively and significantly while policy also tookplace as moderator variable. The result of the test showed that policy moderated competence andperformance which mean the higher competence and policy were followed by greater performanceconversely.